The Spiritual Director in Orders of Monks: A Canonical Analysis - MARONEY, Nicholas (Université d'Ottawa | University of Ottawa, 2025)
Spiritual direction enjoys a prominent place within the monastic vision and ascetical discipline. Monks, however, have struggled to answer one simple question: Who is a monk’s spiritual director? Over the long development of universal and proper law and monastic customs, various answers have emerged sometimes emphasizing the superior’s spiritual paternity, at other times emphasizing the common good and discipline of the religious institute, and still at other times, especially in recent history, emphasizing the freedom of conscience as an application of the right to privacy. Since the Second Vatican Council has given religious a dual mandate for reform in Perfectœ caritatis to return to the sources and make suitable adaptations in the contemporary context, the canonical analysis of the spiritual director in orders of monks offers a tangible pattern of how the historical notion of the spiritual director can be adapted to the ius vigens without conflation of the fora and spiritual abuse. This dissertation, therefore, purposes to analyze the canonical norms governing the spiritual director, to identify the resultant challenges in post-conciliar monasticism, and therefrom to offer a legal opinion of what might be done in orders of monks to address licitly these challenges in practice. Methodologically, this study commences with the historical evolution of the spiritual director from nascency in the desert experience and as promulgated in the monastic rules (chapter one) before considering the juridic treatment of the spiritual director in the 1917 and 1983 codifications (chapter two). Finally, the study considers the spiritual director post-codification in Church documents and monastic custom (chapter three) before surveying practical circumstances to offer a canonical appraisal and modest suggestions towards greater canonical observance (chapter four).
Keywords: spiritual director; spiritual direction; orders of monks; monasticism; monk; canon law; proper law; canon 630